High-fidelity simulation in sepsis and septic shock for medical students of a private university in Lima, Peru - Mas Ubillús, Guiliana (2025)
Objective: to evaluate the impact of a program on high-fidelity simulation on knowledge about sepsis and septic shock among pre-graduate medical students. Methods: A quasi-experimental study was conducted. Students received lectures on sepsis and septic shock before the simulation sessions. Two sessions were scheduled, one on sepsis due to an upper urinary tract infection (scenery A) and the second one about septic shock due to nosocomial pneumonia (scenery B). A pre-and post-test was scheduled, and a debriefing was guided by a checklist to evaluate the achievement of the learning objectives. Results: 153 students participated; the mean score of the post-test was higher than the pre-test (0.97± 0.06 vs. 0.90 ± 0.14 p<0.00). The most right topic in the pre and post-test was determining gold time in sepsis and septic shock (98% on the pre-test and 100% on the post-test). The less correct item on the checklist was the evaluation of diuresis (50% and 35%, respectively). Conclusions: High-fidelity simulation sessions improve pre-graduated medical students' knowledge of sepsis and septic shock.